Cardiovascular implications of gender-affirming hormone treatment in the transgender population. (November 2019) - Dutra, Erika; Lee, Julie; Torbati, Tina; Garcia, Maurice; Merz, C. Noel Bairey; Shufelt, Chrisandra
Highlights: Cardiovascular disease is the leading disease-specific cause of death for transgender people. Cross sex hormone therapy necessary to achieve physical change comes with specific implications and risks related to cardiovascular disease. Transgender woman using cross sex hormone therapy have the highest risk of cardiovascular death than all other groups. Research on the long-term health effects of CSHT beyond 10-years of use is needed. Abstract: Transgender men and women represent a growing population in the United States and Europe, with 0.5% of adults and 3% of youth identifying as transgender. Globally, an estimated 0.3–0.5% of the population identify as transgender. Despite the increasing percentage of individuals whose gender identity, gender expression and behavior differ from their assigned sex at birth, health outcomes in transgenders have been understudied. Many transgender people seek treatment with cross-sex hormone therapy starting from a young age and frequently at high doses in order to obtain the secondary sex characteristics of the desired gender. There is a need to understand the potential long-term health consequences of cross-sex hormone therapy, given that cardiovascular disease is the leading disease-specific cause of death in this population. This review discusses the cardiovascular risks of gender-affirming hormone treatments with respect to transgender women and transgender men.